Current Status and Survival Impact of Infectious Disease Consultation for Multidrug-Resistant Bacteremia in Ventilated Patients: A Single-Center Experience in Korea - Kim, Insu; Kim, Won-Young; Jeoung, Eun Suk; Lee, Kwangha (Acute and critical care, 2018)
We evaluated the current status and survival impact of infectious disease consultation (IDC) in ventilated patients with multidrug-resistant (MDR) bacteremia. One hundred sixty-one consecutive patients from a single tertiary care hospital were enrolled over a 5-year period. Patients with at least one of the following six MDR bacteremias were included: methicillin-resistant , extended-spectrum β-lactamase-producing gram-negative bacteria ( and ), carbapenem-resistant gram-negative rods ( and ), and vancomycin-resistant Enterococcus faecium. Median patient age was 66 years (range, 18 to 95), and 57.8% of subjects were male. The 28-day mortality after the day of blood culture was 52.2%. An IDC was requested for 96 patients based on a positive blood culture (59.6%). Patients without IDC had significantly higher rate of hemato-oncologic diseases as a comorbidity (36.9% vs. 11.5%, P < 0.001). Patients without an IDC had higher Acute Physiology and Chronic Health Evaluation (APACHE) II score (median, 20; range, 8 to 38 vs. median, 16; range, 5 to 34, P < 0.001) and Sequential Organ Failure Assessment (SOFA) score (median, 9; range, 2 to 17 vs. median, 7; range, 2 to 20; P = 0.020) on the day of blood culture and a higher 28-day mortality rate (72.3% vs. 38.5%, P < 0.001). In patients with SOFA ≥9 (cut-off level based on Youden's index) on the day of blood culture and gram-negative bacteremia, IDC was also significantly associated with lower 28-day mortality (hazard ratio [HR], 0.298; 95% confidence interval [CI], 0.167 to 0.532 and HR, 0.180; 95% CI, 0.097 to 0.333; all P < 0.001) based on multivariate Cox regression analysis. An IDC for MDR bacteremia was requested less often for ventilated patients with greater disease severity and higher 28-day mortality after blood was drawn. In patients with SOFA ≥9 on the day of blood culture and gram-negative bacteremia, IDC was associated with improved 28-day survival after blood draw for culture.